1991
DOI: 10.1101/gad.5.12a.2303
|View full text |Cite
|
Sign up to set email alerts
|

The product of the yeast UPF1 gene is required for rapid turnover of mRNAs containing a premature translational termination codon.

Abstract: mRNA decay rates often increase when translation is terminated prematurely due to a frameshift or nonsense mutation. We have identified a yeast gene, UPF1, that codes for a trans-acting factor whose function is necessary for enhanced turnover of mRNAs containing a premature stop codon. In the absence of UPF1 function, frameshift or nonsense mutations in the HIS4 or LEU2 genes that normally cause rapid mRNA decay fail to have this effect. Instead, the mRNAs decay at rates similar to the corresponding wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
465
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(484 citation statements)
references
References 26 publications
17
465
2
Order By: Relevance
“…We generated northern-blot probes by RT-PCR (primer sequences available on request) and carried out hybridizations with UltraHyb (Ambion). We quantified radioactive signals using an Instant Imager (Packard) and calculated halflives as described 29 .…”
Section: Methodsmentioning
confidence: 99%
“…We generated northern-blot probes by RT-PCR (primer sequences available on request) and carried out hybridizations with UltraHyb (Ambion). We quantified radioactive signals using an Instant Imager (Packard) and calculated halflives as described 29 .…”
Section: Methodsmentioning
confidence: 99%
“…As the target tissue was not available, it is unknown how this variant can affect the structure of the IQSEC2 protein. The most likely option is the degradation of the mRNAs containing PTCs by the NDM pathway (Leeds et al; 28 for a review see Kervestin and Jacobson 29 ). Regarding clinical features in females, these are less severe due to the presence of a normal X-chromosome, which has been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…The nonsense-mediated mRNA decay (NMD) pathway is a cellular quality control mechanism that degrades aberrant mRNAs harboring premature termination codons (Losson & Lacroute, 1979;Gozalbo & Hohmann, 1990;Maquat, 1995;Caponigro & Parker, 1996;Jacobson & Peltz, 1996;Ruiz-Echevarria et al+, 1996;Weng et al+, 1997)+ This mRNA surveillance pathway functions in all eukaryotic systems examined and appears to have evolved to recognize premature termination events during the protein synthesis process (Pulak & Anderson, 1993;Weng et al+, 1996aWeng et al+, , 1996bWeng et al+, , 1998Czaplinski et al+, 1998Czaplinski et al+, , 1999+ Several genes required for NMD have been identified in the yeast Saccharomyces cerevisiae+ Mutations in the UPF1, UPF2, UPF3, MOF2/SUI1, MOF5, MOF8, and HRPI genes were shown to selectively stabilize mRNAs containing early nonsense mutations without affecting the decay rates of most wild-type mRNAs (Leeds et al+, 1991(Leeds et al+, , 1992Cui et al+, 1995Cui et al+, , 1999He & Jacobson, 1995;Lee & Culbertson, 1995;Gonzalez et al+, 2000)+ Subsequently, Upf1p, Upf2p, and Upf3p were shown to form a complex (He & Jacobson, 1995;Weng et al+, 1996b;He et al+, 1997)+ In other studies using Caenorhabditis elegans, Smg genes were identified whose products were shown to be involved in NMD and a subset of those are homologous to the yeast UPF genes (Pulak & Anderson, 1993;Cali & Anderson, 1998)+…”
Section: Introductionmentioning
confidence: 99%
“…The yeast UPF1 gene and its protein product have been the most extensively investigated factor in the NMD pathway (Altamura et al+, 1992;Koonin, 1992;Leeds et al+, 1992;Atkin et al+, 1995Atkin et al+, , 1997Czaplinski et al+, 1995Czaplinski et al+, , 1999Cui et al+, 1996;Weng et al+, 1996aWeng et al+, , 1996bWeng et al+, , 1998)+ The Upf1p contains a cysteine-and histidine-rich region near its amino terminus and all the motifs of the superfamily group I helicases+ The yeast Upf1p has been purified and demonstrated to have RNA-binding activity, RNA-dependent ATPase activity, and RNA helicase activity (Czaplinski et al+, 1995, Weng et al+, 1996a, 1996b)+ Disruption of the UPF1 gene results in stabilization of nonsense-containing mRNAs and suppression of certain nonsense alleles (Leeds et al+, 1991;Cui et al+, 1995;Czaplinski et al+, 1995;Weng et al+, 1996aWeng et al+, , 1996b)+ A set of mutations was isolated in the UPF1 gene that separated its mRNA decay function from its activity in modulating translation termination at a nonsense codon (Weng et al+, 1996a(Weng et al+, , 1996b)+ Consistent with the view that the Upf1p is involved in modulating translation termination, recent results have shown that it interacts with the translation termination release factors eRF1 and eRF3 (Czaplinski et al+, 1998(Czaplinski et al+, , 1999)+ These data suggest that the NMD and translation termination pathways are linked (reviewed in Czaplinski et al+, 1998Czaplinski et al+, , 1999)+ Based on these observations, a "surveillance complex" consisting of at least Upf1p, Upf2p, Upf3p, and the release factors has been suggested to modulate translation termination and NMD (Czaplinski et al+, 1998(Czaplinski et al+, , 1999)+ Homologs of the Upf1p have been identified in humans cells (the HUPF1/RENT gene; Perlick et al+, 1996, Applequist et al+, 1997 and in C. elegans (Page et al+, 1999;Jacobson & Peltz, 1996; WORMPEP: Y48G8A 3304+a)+ It is evident that the Upf1p plays a conserved role in NMD...…”
Section: Introductionmentioning
confidence: 99%